Are We Prepared for the Next Disaster? Evidence from Ice Storm - Asgary, Ali; Vaezi, Ali; Azimi, Nooreddin (TDMRC, Universitas Syiah Kuala, 2021)
This study examines the impacts that an emergency had on peoples preparedness levels, using the December 2013 Ice Storm in the Greater Toronto Area (GTA) as a case. A questionnaire consisting of three sections was developed to measure the associated impacts, peoples reactions/opinions, as well as their preparedness levels before and after the ice storm. The goal of the research is not only to discuss the factors that influenced peoples ability to prepare, respond to and recover from the ice storm but also to generate useful insights for future disasters that are similar in nature. Our analysis includes various aspects such as the effectiveness of advance warnings and their ability to disseminate information to mass audiences. The findings show that, most of the respondents believe that they learned a lot about ice storms and their impacts because of their prior experience; a significant majority believe that it is the citys/municipalitys responsibility to prepare for emergencies like ice storms; home ownership was significantly associated with the previous ice storm preparedness; and, power outage experience was significantly associated with the next ice storm preparedness.